The Chemical Syntheses of Nannocystins - Wang, Zhang (Synthesis, 2019)
The broad and potent anticancer activity of the nannocystin family of natural products has attracted significant efforts toward their total syntheses. Currently, seven total syntheses of different members of the nannocystins have been reported. In this Short Review, different synthetic approaches are highlighted. The reported structure-activity relationship (SAR) studies will also be highlighted.
Keywords: nannocystin; total synthesis; depsipeptide; SAR studies; elongation factor inhibitor